IDENTIFICATION OF ORGANIC COMPOUNDS FROM EXTRACT LOTUS SEEDS (Nelumbo nucifera) (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2019)
Abstract. Seeds of Nelumbo nucifera is many found in Indonesia. South Sulawesi is one of the most potencial provine swamp of Indonesia. The Phytochemical test of this plant contain of alkaloid, tanin, saponin, steroid, terpenoid and flavonoid from methanol exract sample, n-hexane, chloroform and ethanol. The result of this phytochemical test is positively contain of terpenoid, tanin, and saponin; chloroform extract positively contain of alkaloid, terpenoid, and tanin; ethanol extract positively contain of flavonoid, tannin, and saponnin; n-hexane extract showed the negative result of this test.
Keywords: Seeds of Nelumbo nucifera; phytochemical test.